Effect of high pressure in starch viscoelastic properties studied with an acoustic wave sensor - Santos, M. D. (2018)
Unmodified native starches lack stability under temperature changes, shear, or pH. Food is often processed in order to induce modifications intended to improve the product and to give it the desired characteristics. Among the physical processing methods, high hydrostatic pressure is considered a mild technique with a big potential and it is nowadays used in a variety of products. Gelatinization of maize starch processed by high pressure was for the first time studied using an acoustic wave sensor. Besides a significant increase in amylopectin fusion temperature, other differences induced by pressure are visible on the frequency vs. temperature plot. Results from currently applied techniques are also shown, as only a combination of methodologies can contribute to a deep understanding of such a complex phenomenon as gelatinization.